Association of COVID-19 severity with body mass index and underlying comorbid conditions-a hospital-based cross-sectional study - Sampath, Raju Kannan; Hussain, Aamina; Subramanian, Venkata Meenakshi; Logaraj, Muthunarayanan (International Journal of Advances in Medicine, 2022)
Background: To reduce the severity of the disease among COVID-19 patients with co-morbidities is the need of the hour. Obesity may contribute to adverse outcomes in coronavirus disease 2019 (COVID-19). This study aimed to find the association between the COVID-19 biomarker values and the underlying comorbid conditions and assess the severity of the disease according to the patients' body mass index (BMI). Methods: A single centre cross-sectional study was conducted in a tertiary hospital among 184 COVID-19 patients admitted for one month (June-July 2021). Results: The results show a statistically significant association between the COVID-19 severity and co-morbidity status of the patients, with diabetes mellitus being the most prevalent co-morbidity among the patients, followed by diabetes with hypertension. A statistically significant association was also seen between age and co-morbidity and biomarkers and co-morbidity. Conclusions: Obesity and other comorbid conditions like diabetes mellitus and hypertension should be given utmost importance during treatment among COVID-19 patients. Biomarker screening should be routinely done in patients with co-morbidities and obesity. Awareness among the COVID-19 patients regarding the comorbid conditions and BMI is the need of the hour.